Hubungan Pola Makan dan Jumlah Leukosit dengan Jenis Apendisitis di RSUD Sungai Dareh - Astuti Ardi Putri (Jurnal Ilmiah Universitas Batanghari Jambi, 2020)
Influence of Lifestyle Lack of consumption of fibrous foods in the daily menu, allegedly as one of the causes of health problems namely appendicitis. Appendicitis is inflammation that occurs in the appendix or appendix. When suffering from appendicitis, sufferers can feel pain in the lower right abdomen. If left unchecked, the infection can become serious and cause appendicitis to rupture, thereby causing severe pain complaints that endanger the lives of sufferers. The incidence of appendicitis in 2014 ranks eighth as the main cause of death in the world and it is estimated that in 2020 will be the fifth leading cause of death worldwide. The purpose of this study was to determine the relationship between diet and the number of leukocytes with the type of appendicitis in Sungai Dareh District Hospital. The number of samples in this study were 32 respondents using the Accidental Sampling technique. Most of the research results were obtained 21 (65.6%) respondents had poor diet, 17 (53.1%) respondents had leukocytosis, 22 (68.8%) respondents had perforated appendicitis, and there was a relationship between eating patterns and Leukocyte count with type of appendicitis.